A clinical audit on diabetes care in two urban public primary care clinics in Malaysia - Shariff Ghazali, Sazlina; Abu Hassan, Zailinawati; Ali, Zaiton; Ong, Ian (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2010)
Introduction: The incidence of diabetes mellitus (DM) is increasing globally and it is associated with significant morbidity and mortality. The importance of a better quality of diabetes care is increasingly acknowledged. Objective: This clinical audit was conducted to assess the quality of care given to type 2 DM patients in public primary care clinics. Methods: A clinical audit was conducted in two selected urban public primary care clinics, between April and June of 2005. The indicators and criteria of quality care were based on the current Malaysian clinical practice guidelines for type 2 DM. A structured pro forma was used to collect data. Results: A total of 396 medical records of patients with type 2 DM were included in this audit. Most of the patients had measurements of fasting blood glucose and blood pressure recorded in more than 90% of the visits over the previous one year. Twenty-seven percent of the patients had glycosylated haemoglobin (HbA1c) done every 6 months with a mean of 8.3%. Only 15.6% had HbA1c values less than 6.5 %. Fifty percent had blood pressure controlled at 130/80 mmHg and below; and 13.0% had low density lipoprotein cholesterol values of 2.6 mmol/L or less. The majority of the patients were overweight or obese. Conclusions: The quality of diabetes care in this study was found to be suboptimal. There is a gap between guidelines and clinical practice. Certain measures to improve the quality of diabetes care need to be implemented with more rigour.